Birth outcomes in Colorado's undocumented immigrant population - Battaglia Catherine; Bublitz Caroline; Westfall John M; Reed Mary M; Fickenscher Alexandra (BMC Public Health, 2005)
Abstract Background The birth outcomes of undocumented women have not been systematically studied on a large scale. The growing number of undocumented women giving birth in the United States has important implications for clinical care and public health policy. The objective of this study was to describe birth outcomes of undocumented immigrants in Colorado. Methods Retrospective descriptive study of singleton births to 5961 undocumented women using birth certificate data for 1998–1999. Results Undocumented mothers were younger, less educated, and more likely to be single. They had higher rates of anemia, were less likely to gain enough weight, and less likely to receive early prenatal care. They were much less likely to use alcohol or tobacco. Undocumented women had a lower rate of low birth weight (5.3% v 6.5%, P < .001) or preterm infants (12.9% v 14.5%; p = .001). Undocumented women experienced higher rates of labor complications including excessive bleeding (2.3% v 0.8%, p < .001) and fetal distress (8.7% v 3.6%, p < .001). Conclusion Undocumented women have lower rates of preterm delivery and low birth weight infants, but higher rates of pregnancy related risk factors. Higher prevalence of some risk factors which are amenable to medical intervention reveals the need for improved prenatal care in this group.